2021
DOI: 10.5210/spir.v2021i0.12088
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Data Cultures

Abstract: This panel deploys a range of qualitative methodologies to investigate how processes of datafication meet with the subjective experiences of ordinary people, and the practices of everyday life. We draw on the model of ‘everyday data cultures’ proposed by Burgess (2017) to explore the ways diverse data practices – including the production and circulation of data visualisations, modes of data storage and vernacular engagements with data literacy – can be understood as aspects of culture. Following Burgess, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The relationships between news organisations and governments were central, as the former sought to inform a highly engaged public about the pandemic using data provided by the latter, delivering daily updates on numbers of cases, hospitalisations and deaths and (later) vaccine doses. Such forms of data-driven reporting became ritualised -that is embedded in the daily rhythms of the news and media environment and citizens' everyday lives (Burgess et al, 2022) -in Australia as in many other countries (Pentzold et al, 2021;Perreault and Perreault, 2021;Tong, 2022;Wu, 2021). The continuous flows of data from a range of sources associated with the public health crisis, and the continuous demand for data-driven reporting, intensified the perceived need for news organisations to accelerate the transition towards automated work practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between news organisations and governments were central, as the former sought to inform a highly engaged public about the pandemic using data provided by the latter, delivering daily updates on numbers of cases, hospitalisations and deaths and (later) vaccine doses. Such forms of data-driven reporting became ritualised -that is embedded in the daily rhythms of the news and media environment and citizens' everyday lives (Burgess et al, 2022) -in Australia as in many other countries (Pentzold et al, 2021;Perreault and Perreault, 2021;Tong, 2022;Wu, 2021). The continuous flows of data from a range of sources associated with the public health crisis, and the continuous demand for data-driven reporting, intensified the perceived need for news organisations to accelerate the transition towards automated work practices.…”
Section: Discussionmentioning
confidence: 99%
“…The journalists and other news workers we interviewed agreed that the pandemic had altered their work routines and that the news cycle had been reshaped by the COVID-19 data environment. Journalists attempting to expedite data processing for their stories indicated that barriers to the use of automation during the pandemic were also related to the lack of appropriate infrastructures and the absence of open 'data cultures' (Burgess et al, 2022) within the government agencies managing COVID-19. One of the principal issues hampering those efforts during the first stages of the pandemic was that data availability and access were politicised by the governments of the day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps we are at a watershed moment and autolography will become part of Western 'everyday data cultures' (Burgess et al, 2022) and new, creative ways of using it will emerge. Or we may also be at the beginning of a period of legal and cultural contestation against these techniques and technologies.…”
Section: Parallels Between Photography and Autolography As 'Magic' Mediamentioning
confidence: 99%
“…In doing so, they drew on the work of cultural and media studies scholars who emphasised how digital and mobile technologies have rapidly become part of mundane, everyday life and what was once strange or alien is now familiar (Baym, 2015;Hartmann, 2013;Pink et al, 2017). Familiarity though tends to co-exist with uncertainties and anxieties about the unruliness of everyday data, which has led to considerations of what it feels like to live with the messiness of data (Burgess et al, 2022;Pink et al, 2018). Deborah Lupton (2016) developed the concepts of visceral data and lively data, which respectively acknowledge how data are felt and experienced and how they are relational to other things.…”
Section: Mundane Datamentioning
confidence: 99%